Calcified Granulomatous Disease: Occupational Associations and Lack of Familial Aggregation - Reed, Robert M. (Lung, 2014)
PURPOSE: The acute host response to histoplasma capsulatum infection varies according to exposure and susceptibility. Late sequelae include calcifications in the lung, thoracic lymphatics, and spleen. Determinants of calcified granuloma formation are poorly studied and may differ from those affecting acute response. We examined the occupational associations and familial aggregation of radiographic calcified granulomatous disease to characterize the determinants of calcified granuloma formation. METHODS: We analyzed prospectively collected cross-sectional data including computed tomograms from 872 adult members of the Old Order Amish of Lancaster County. RESULTS: Granulomas were present in 71 % of participants. Granulomas were present in the lung of 57 % of participants, in the hilar or mediastinal lymph nodes of 55 % of participants, and in the spleen of 29 % of participants. No significant differences were observed in the presence of granulomas between men and women. Each year of age was associated with 4 % higher odds of splenic calcifications, and a primary occupation of farming was associated with an 84 % higher odds of splenic calcifications. A compelling pattern of familial aggregation was not observed. CONCLUSIONS: Calcified granulomatous disease does not appear to aggregate in families. Determinants influencing patterns of granulomatous disease include occupation, age, and geographic location.